NATURAL AND ARTIFICIALLY STIMULATED RADIATION PROCESSES IN QUARTZ: SIMILARITIES AND DIFFERENCES - Rakov L.T. (My University, 2003)
The problem of the correspondence of natural and artificially stimulated radiation processes in quartz was addressed. It was shown, using the radiation accumulation of Al-O- and Ti centers as an example, that this problem can be solved on the basis of the concept of sparring defects. As a working model, it was proposed that the major factor responsible for the formation of an electron-hole center in a mineral is charge stabilization. The kinetics of center accumulation in quartz under the influence of artificial irradiation and weak and strong natural radiation were studied and interpreted. We determined the range of radiation doses under which the natural and artificially stimulated accumulation processes of Al-O--centers can be considered as mutually adequate. It was shown that different mechanisms of center accumulation operated in the deep and near-surface zones of quartz grains from sedimentary rocks. It was suggested that the radiation history of quartz can be unraveled using the concentrations of centers in these zones.